Gaukang and White Coup: Dismantling of Traditional Power - Nila Sastrawati (Jurnal Ilmu Sosial dan Ilmu Politik, 2017)
This paper discusses the concept of power adhered to by the South Sulawesi community and explains the power struggle which had occurred both in the past and present. The South Sulawesi community’s conceptiontraditional power on power signifies a strong, transcendental relationship between themselves and supernatural powers, wherein all objects possessing certain peculiarities are inseparable from the stable and unchanging cosmic world. Thus, gaukang holds a significant position in the life of the South Sulawesi community, particularly pertaining to matters of power struggle. The waxing and waning of traditional power in South Sulawesi is determined by at least three factors: firstly, a change in power patterns with the emergence of new elites having a commoner background; secondly, incessant resistance to feudalistic rule; and lastly, the application of modern bureaucratic model. The general conclusion of this paper emphasizes the position of gaukang as a central point affecting the various power struggles that occurred throughout the history of the South Sulawesi community. The enactment of Regional Regulation (Perda) No. 5 year 2016 on the Organization of Gowa Regency Local Cultural and Customary Institution provides a peek at how bureaucratic power had dismantled traditional power in Gowa Regency, which included, consequently, the transfer of authority over the royal heirlooms or gaukang of the Gowa Kingdom.